BRAND AWARENESS ANALYSIS TOWARD PURCHASE DECISION MAKING IN GAMING COMPUTER INDUSTRY (A Case Study of Allienware-Dell Gaming Laptop) - Mario Dwikirama Giffels; Nila Krishnawati Hidayat; Linus . Pasasa (Jurnal Dinamika Manajemen, 2013)
The first purpose of this research is to analyze the level of Brand Awareness of Alienware consumers toward Purchasing Decision Making. The second purpose is to analyze the most influential factor inPurchase Decision Factor, and the last purpose is to analyze the correlation between Brand Awareness and its Purchasing Decision. To support this research, the author made an interview with the General Manager of one of Alienware retail store in South Jakarta and handed 100 questionnaires to target market. As a result, Situational Factor found to be the most influencing factor in Alienwareconsumer Purchasing Decision toward Brand Awareness. It is Â also found that the level of BrandAwareness is high for Alienware target market. Finally it is concluded that there is a correlation between Brand Awareness and Purchasing Decision Making. Â  Keywords: Brand Awareness, Brand Recognition,Purchasing Decision Making, Luxury Product, Situational factor